PENDIDIKAN ISLAM DI AUSTRALIA - M. Ridho; Walhadi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Australia, although geographically close to Asia, still maintains cultural closeness to the Western world. The majority of the population adheres to Christianity, but Islam has developed rapidly in this country. The growth of Islam in Australia cannot be separated from the active role played by the Muslim community, which consists of individuals who migrated to Australia for various reasons such as economic and political motives. To integrate and preserve their Islamic identity, Muslims in these communities make various efforts. Based on this background, this article discusses Australian history, the origins of the Australian population, the history of Islam in Australia, Islamic education in Australia.